Public stigma profile toward mental disorders across different university degrees in the University of Valencia (Spain) - Ruiz, Juan C.; Fuentes-Durá, Inmaculada; López-Gilberte, Marta; Dasí, Carmen; Pardo-García, Cristina; Fuentes-Durán, María C.; Pérez-González, Francisco; Salmeron, Ladislao; Soldevila-Matías, Pau; Vila-Francés, Joan; Balanza-Martínez, Vicent (Frontiers in Psychiatry, 2022)
Background: A large proportion of studies carried out in recent years in different populations have shown that stigma toward mental disorders is highly prevalent. In the present study we conducted a comprehensive assessment of stigma to describe and compare stigma toward mental disorders in students enrolled in five different university degrees. Methods: Three hundred and twenty-five students from the University of Valencia (Spain), attending the second term of their first-degree courses in the faculties of medicine, psychology, teaching, economics, and data science participated in this cross-sectional study. Stigma was measured using: the Reported and Intended Behavior Scale (RIBS), the Scale of Community Attitudes towards Mental Illness (CAMI), the Attribution Questionnaire (AQ-27), and the Knowledge about Mental Illness test (KMI). Results: We found different patterns of stigma according to gender, the fact of knowing or living with a person with mental disorders and the university degree studied. Overall, women show fewer stigmatizing attitudes than men but similar stereotypes and prejudice towards people with mental disorders. However, the pattern of results across degrees is more complex. Overall, students of medicine, psychology and teaching showed fewer stigmatizing attitudes than students of economics and data science but differences between degrees were more subtle in stereotypes and prejudice towards people with mental disorders. Conclusion: Our study suggests the existence of different profiles of stigma in relation to mental disorders in university students. These profiles varied in relation with the degree being studied, gender and already knowing or living with a person with mental disorders.